Integrating Maqasid al-Shariah into Higher Education: Enhancing the Role of Faculty in Achieving the SDGs - Shalghoum, Najimudin; Yahya, Najeeb; Abdullah, Mahmoud; Masuwd, Mowafg; Kasheem, Majdy; Alrumayh, Safa; Aryanti, Yosi; Rosyadi, Nabil (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
This study examines the potential of Maqasid al-Shariah as an ethical and educational framework for enhancing the role of faculty members at the University of Zawia in supporting the Sustainable Development Goals. A structured questionnaire was administered to 100 lecturers across various disciplines, and the data were analyzed using descriptive statistics. The findings reveal moderate awareness of the Sustainable Development Goals, strong recognition of the relevance of maqasid, but limited institutional implementation in curriculum, governance, and community outreach. Key challenges include insufficient training for lecturers, weak institutional strategies, and limited administrative support. The study contributes a localized model for integrating Islamic ethical values with global development goals and highlights concrete policy implications for strengthening faculty development, curriculum reform, and institutional planning within the Libyan higher education context.